Perceived Academic Satisfaction of Fourth-Year Pre-Service Teachers - Bernadette L. Soliba; Maria Le Ann D. Rivera; Aireena Joyce M. Marquez; Alyssa Mae B. Marquez; Julia P. Ocumen; Brechelle B. Ottao; Rochelle B. Pedro; Manuel T. Posot; Kyneschi E. Ramos; Gail Rhea E. Rivera (SAGE Open)
The present study aimed to determine the academic satisfaction of fourth-year pre-service teachers at Saint Louis University. It elaborates on the different satisfaction levels and factors regarding the student’s academic performance. The study utilized a mixed-method design, a questionnaire, and an interview for data collection. Through the sampling method, 72 4th-year Education Students enrolled at Saint Louis University, Baguio City, for the first semester of the academic year 2022 to 2023 were the respondents of the study. Specifically, the School of Teacher Education and Liberal Arts (STELA) was involved in the study. The findings of this study have important implications for teacher education programs. With the use of the mixed method, the researchers were able to determine two notable factors that ranked first on the satisfaction of the pre-service teachers. The results imply that the majority of pre-service teachers were satisfied with their academic experience. They were satisfied with the teaching quality and the resources offered to help them learn.